Pengaruh Model Discovery Learning Terintegrasi Budaya Tu’dang Sipulung Terhadap Hasil Belajar IPAS Siswa Kelas IV UPT SD Inpres Sarite’ne Kabupaten Gowa - Salsabila Pratiwi; Suardi; Fitri Yanty Muchtar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of the discovery learning model integrated with tu'dang sipulung culture on the science learning outcomes of fourth grade students of UPT SD Inpres Sarite'ne, Gowa Regency. This study is a quantitative study with a quasi-experimental research type. The population in this study were all fourth grade students of UPT SD Inpres Sarite'ne, Gowa Regency, totaling 50 students. The sample in this study was 50 students, consisting of 25 classes IVA as the experimental class and 25 classes IVB as the control class. The instruments in this study were observation sheets and tests. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. Based on the results of the study and data analysis, it can be concluded that there is an effect of the discovery learning model integrated with tu'dang sipulung culture on the science learning outcomes of fourth grade students at UPT SD Inpres Sarite'ne, Gowa Regency. This is confirmed by the results of the independent sample t-test, which obtained a calculated t value of 3.338 and a t table of 2.010, so the calculated t> t table = 3.338> 2.010 or a sig value (2-tailed) of 0.002, so 0.002 <0.05 was obtained. In addition, the learning outcomes of students in the experimental group using the tu'dang sipulung culture integrated discovery learning model increased where in the pretest there were 5 students with a percentage of 20% who achieved a passing grade, while in the posttest there were 25 students with a percentage of 100% of students achieving a passing grade. Based on the results of the study, it can be concluded that there is an influence of the tu'dang sipulung culture integrated discovery learning model on the learning outcomes of class IV students of UPT SD Inpres Sarite'ne, Gowa Regency.